Professional utilization in academic libraries a survey of eleven selected private colleges and universities in Metro Manila - Mallillin, Rogelio B.; Santos, Herminia H.; Tamesis, Angelina R. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1986)
The general objective of this study is to determine the librarians' role in selected colleges and universities within Metro Manila. Specifically, the study aimed to find out the professional and non-professional work involvement of 86 librarians, respondents to a questionnaire especially designed for the purpose. The ultimate objective was to see if some guidelines could be set in the assignment of clerical and professional work activities in academic libraries.
With the attainment of the above objectives, it was hoped that library administrators would find the study helpful in properly assigning work of library personnel to avoid overlapping of duties and misutilization and/or underutilization of professional staff. Under these favorable situations librarians would function to the best interest of their respective libraries, and be duly recognized as professionals in their own right.
The study employed the survey and interview method. Ocular investigation of the libraries surveyed was also conducted. The main part of the questionnaire was a checklist of all possible library tasks arranged alphabetically. Each activity carried a value reflective of its degree of professionalism within library parlance. Respondents were free to check as many as few items as are applicable to themselves. The reported activities were analyzed following a pattern of arriving at an index score for each respondent. Professional utilization in each library surveyed was statistically figured out. Summary figures for special groupings were also determined.
The general conclusion was professional utilization in the libraries surveyed was less than optimal. Librarians qualified to perform high-level activities by virtue of their education and training were assigned clerical duties. It was also found out that the six libraries (out of the 11 surveyed) which employed more librarians than clerks ended up with negative index scores. This meant that non-professional tasks were assigned and handled by the professional staff on a regular basis. Most of these inconsistencies and malpractices were traced to their job descriptions.
There was also this misconception by two-thirds of the 86 respondents about the type of responsibilities they ought to handle. They believed that clerical duties in libraries have to be performed by librarians to ensure the accurate performance of such. It can be discerned that these librarians did not serve their respective libraries and clientele in the best way possible. In the process, they degraded their academic status and the librarianship profession in general.
Typescript.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: College librarians -- Philippines -- Manila Metropolitan Area; Libraries, University and colleges -- Philippines -- Manila Metropolitan Area